2020
DOI: 10.24259/fs.v4i2.9687
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Climate Variability and Burned Area in Borneo using Clustering Methods

Abstract: The island of Borneo has faced seasonal forest fires for decades. This phenomenon is worsening during dry seasons, especially when droughts are concurrent with the El Niño-Southern Oscillation (ENSO) phenomenon. Climate is therefore one of the drivers of the fire phenomenon. This paper studies the relationship between climate variables, namely temperature, precipitation, relative humidity, and wind speed, and the occurrence of forest fire using two clustering methods, K-means and Fuzzy C-means (FCM) clustering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The same incident happened again in 2014/2015 [2]. The study results in [4] also showed that the climate variable strongly correlates with fires in Borneo.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The same incident happened again in 2014/2015 [2]. The study results in [4] also showed that the climate variable strongly correlates with fires in Borneo.…”
Section: Introductionmentioning
confidence: 83%
“…There are many studies about forest fires that implement machine learning, as described in [4], [5], [6]. The problem domains in those studies also vary, from fire detection to planning and policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1997/1998 ENSO-driven fire in Sumatra and Kalimantan was the most studied. In general, climatic factors significantly affect the occurrence of fires (Brasika, 2022;Hidayati et al, 2020). ENSO-related fires have encouraged more scientific inquiries in Indonesia and other tropical countries (Alencar et al, 2006;Juárez-Orozco et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…study by [6] shows that the relative humidity contributes most to the burned area in Kalimantan. Meanwhile, revegetation is able to maintain a vegetation cover on peat and increasing humidity in the soil and air, slowing peat decomposition and also decreasing fire risks, thus becoming the second important tenet of peatland restoration after restoration of the hydrology [7].…”
Section: Introductionmentioning
confidence: 99%